2020
DOI: 10.1038/s41598-020-78034-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar and soil application of plant growth promoting bacteria on growth, physiology, yield and seed quality of maize under Mediterranean conditions

Abstract: The use of plant growth promoting bacteria (PGPB) as biostimulants favors the increase of crop productivity and the improvement of yield quality. The main objective of the present study was to investigate the effect of the PGPB biostimulants (Azotobacter chroococcum, Bacillus subtilis, Bacillus megatherium and their mixes) and the application method (foliar and soil) on the growth, the physiology, the yield and the quality of maize. The obtained results showed that A. chroococcum treatment increased the chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…The implementation of plant biostimulants in many plant species is a promising practice that was used over the last decades [ 1 , 2 ]. Plant biostimulants can be microorganisms such as species and strains of beneficial bacteria as well as any substances that can stimulate the performance of plants by increasing their nutrition efficiency, abiotic stress tolerance, and their quality traits [ 3 , 4 , 5 ]. Plant growth promoting bacteria (PGPB) is a promising category of biostimulants that showed positive interaction in some plants, and thus, gained the interest of the researchers worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of plant biostimulants in many plant species is a promising practice that was used over the last decades [ 1 , 2 ]. Plant biostimulants can be microorganisms such as species and strains of beneficial bacteria as well as any substances that can stimulate the performance of plants by increasing their nutrition efficiency, abiotic stress tolerance, and their quality traits [ 3 , 4 , 5 ]. Plant growth promoting bacteria (PGPB) is a promising category of biostimulants that showed positive interaction in some plants, and thus, gained the interest of the researchers worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Efthimiadou et al [ 3 ] evaluated several PGPB biostimulants in terms of growth, yield, and quality characteristics of maize plants as well as the application method that was used. They concluded that the soil inoculation of bacteria presented better results than the control.…”
Section: Introductionmentioning
confidence: 99%
“…Total protein content of all samples was determined according to Kjeldahl method (IDF, 2008) using a Kjeldahl rapid distillation unit (Protein Nitrogen Distiller DNP-1500-MP, RAYPA, 08227 Terrassa, Barcelona, Spain). Total fiber content of both samples was measured by applying the Weende Method (AOAC 984.04) with some modifications [26] using a manual crude fiber analyzer (FibreBag-Fibretherm, Gerhardt analytical systems, 53639 Königswinter, Germany).…”
Section: Analysis Of Nutritional Compoundsmentioning
confidence: 99%
“…Although there are differences in the mechanism of induction, some of the signaling components for SAR and ISR overlap (Cecchini et al, 2019b(Cecchini et al, , 2015Pieterse et al, 1996Pieterse et al, , 1998Beckers and Conrath, 2007;Beckers et al, 2009). Beneficial rhizobacteria not only induce ISR, but also stimulate the growth and productivity of plants and impact the root system architecture (Berendsen et al, 2012;Efthimiadou et al, 2020). A crosstalk between the signaling pathways of rhizosphere-induced growth promotion and ISR remains unknown.…”
Section: Introductionmentioning
confidence: 99%